Optimizing Wireless Network based on Building Design in Telkom University - Muhammad Fathinuddin; Umar Yunan Kurnia Septo Hediyanto; Aurora Margaretha Rompas; Muhammad Hibban Mikhail (School of Industrial and System Engineering, Telkom University, 2023)
Computer network designed according to its functions and building design which must be analyzed toconsider usage intensity and maintenance. This paper’s study case is in one of the buildings in University atBandung which uses fiber optic and wireless network for both 2,4GHz and 5GHz frequencies. Existingconditions were tested in site surveys which are high frequency interference of wireless signals,misconfigured channel bands caused frequent disconnections close to two different access points, and thereare blank spots causing user’s devices cannot properly connect to network. Wireless network optimizationneeds to be done to solve its problems. Method used is the Network Development Life Cycle (NDLC) whichconsists of Analysis, Design, and Simulation Prototyping phases, and performance measurements usingQuality of Service (QoS) parameters. Site survey results showed many high interference areas caused bychannel misconfiguration in each access point that the same channel can be used for adjacent access points,misplacing wall-mounted access points on ceiling which can interfering both upper floor and lower floornetworks. QoS performance measurements to match TIPHON Standardization for throughput is higher than1kbps, packet loss lower than 3%, and delay lower than 150ms. Recommendation for optimizing network isproperly configuring channel band using non-overlapping channel configuration (1-6-11) for all adjacentaccess points, and there is simulation for replacing wall-mounted access points that placed on the ceiling toa ceiling-mounted type access point. It showed a decreasing interference in the entire network, whether itson the same floor or between upper and lower floor.